The use of neutrophil CD64 and monocyte HLA-DR sepsis index in the diagnosis of neonatal sepsis - Sherif Alanwary; Rana Bakir; Rabab El Hawary; Mohamed Hashim (Egyptian Pediatric Association Gazette, 2022)
Abstract Background Neonatal septicemia remains one of the main causes of neonatal morbidity and mortality. However, there are challenges hindering the early diagnosis. Results nCD64 percent and MFI were not of statistical significance between the confirmed sepsis, clinical sepsis, and control groups (p = 0.453 and 0.149, respectively); meanwhile, the mHLA-DR percent and MFI were both of statistical significance (p = 0.001, 0.0001, respectively) with lower values in the proven sepsis group. Calculating the sepsis index, its value was 74.1% ± 45 SD in the control, 105.5% ± 73 SD probable sepsis group, and 180.6% ± 143 SD in the proven sepsis group; this was of a high statistical significance (p = 0.0001). Conclusion HLA-DR expression on monocytes and nCD64/mHLA-DR sepsis index are reliable indices for the early diagnosis of neonatal sepsis. The sepsis index could be feasibly analyzed by automated flow cytometry even in developing countries. In the future, these markers should be widely assessed as their results are rapid, reliable, and of low cost.